CRETACEOUS SCLERACTINIAN CORAL PREVERASTRAEOPSIS GEN. N. FROM CENTRAL GREECE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The aulastraeoporid coral Preverastraeopsis gen. n.represented by one species Phyllocoenia  major Hackemesser, 1936 from the Cenomanian (?Aptian-Cenomanian) of Central Greece is described. The new genus, characterized by astreoid colony structure is not known to date in the family Aulastraeoidae Alloiteau. The genus is related to Preverastraea Beauvais, which differs from Preverastraeopsis by cerioid colony with corallite wall in structural continuation with the septa.In the latter the radial elements are of costo-septal type, free in their external ends.
Keywords: Scleractinian corals; Aulastraeoporidae; Cretaceous; Central Greece